Principles and Practices of Aquatic Law. - Fletemeyer, John Robert (Boca Raton, FL : CRC Press, 2017)
"This book presents the best practices and principles related to aquatic law and risk management. Its focus is injury and death occurring in aquatic environments including the ocean, pools, water parks, canals, rivers, lakes, dams, etc. It discusses the importance of aquatic risk management as it relates to aquatic accident prevention and the concept of duty and liability for a facility's management and staff. It also presents updated and relevant information about beach safety and the importance of hazard identification, warning, and elimination, and provides information for attorneys relating to the process of developing liability theories involving serious aquatic accidents and death."--Provided by publisher.
Chapter 1 An Overview of Aquatic Law / Michael Flynn -- chapter 2 Legal Concepts, Drowning, and Lifeguard Effectiveness / John R. Fletemeyer -- chapter 3 Principles of Aquatic Risk Management from a Legal Perspective / John R. Fletemeyer -- chapter 4 Evidence Collection and the Daubert Standard / Lori St John -- chapter 5 Swimming Pool and Spa Safety / John R. Fletemeyer -- chapter 6 Headfirst Recreational Aquatic Accidents / Tim O{u2019}Brien -- chapter 7 Ocean Beaches, Lakes, Quarries, Springs, and Canals / John R. Fletemeyer -- chapter 8 Commercial Whitewater Rafting / Julie Munger -- chapter 9 Breaux v. City of Miami Beach, 899 So.2d 1059 (Fla. 2005) / Howard Pomerantz -- chapter 10 Past Its Prime -- The 1920 Death on the High Seas Act / Michael D. Eriksen -- chapter 11 Justice for Deaths Caused by Free-Living Amebae in Recreational Waters / Roger W. Strassburg -- chapter 12 The Psychological Evaluation -- Trauma Caused by a Serious Aquatic Injury or Fatal Drowning / Diana P. Sullivan -- chapter 13 Drowning Forensics, Drowning and Accident Reenactments, and Case Research / John R. Fletemeyer -- chapter 14 Boating and SCUBA Accidents, Low-Head Dams, and Beach Renourishment / John R. Fletemeyer -- chapter 15 Hydrodynamic Analysis of Drowning Events / Brian K. Haus.
OCLC-licensed vendor bibliographic record.
Keywords: Liability for sports accidents -- United States; Aquatic sports -- United States; Water -- Law and legislation -- United States; Liability for marine accidents -- United States; Evidence, Expert -- United States